2009
DOI: 10.1177/0091270009336736
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate Has Positive Hypocholesterolemic and Hypotriglyceridemic Effects: New Data

Abstract: Many psychotropic drugs may affect plasma lipids profile and their metabolism, with carbamazepine being the best known among them. Methylphenidate is a piperidine derivative structurally related to amphetamines and acts as a central nervous system stimulant. Its effect on lipid metabolism has not been investigated. The authors evaluated how methylphenidate affects the lipid profile in the plasma of patients diagnosed as having attention-deficit hyperactivity disorder (ADHD). All consecutive patients undergoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 13 publications
(19 reference statements)
1
18
0
Order By: Relevance
“…Mg, HDL and Apob are the sharpest discriminators between ADHD and Ctr groups. reported by Charach et al (2009): they found decreasing Chol, LDL and TG, but no signifi cant changes in the HDL levels. Hightened physical activity is described to be related to higher HDL concentrations (Korsten-Reck et al 2008;Hamer and Stamatakis 2009).…”
Section: Resultsmentioning
confidence: 80%
“…Mg, HDL and Apob are the sharpest discriminators between ADHD and Ctr groups. reported by Charach et al (2009): they found decreasing Chol, LDL and TG, but no signifi cant changes in the HDL levels. Hightened physical activity is described to be related to higher HDL concentrations (Korsten-Reck et al 2008;Hamer and Stamatakis 2009).…”
Section: Resultsmentioning
confidence: 80%
“…However, the effect of psychostimulants on brain cholesterol content has yet to be directly measured. There is only one report on methylphenidate-mediated change in brain cholesterol level [25]. In this study, a single injection of methylphenidate to male Swiss mice reduced [2-3H] acetate (a sterol precursor) incorporation into brain cholesterol during the 24-hr period examined, suggesting that the pharmacological action of methylphenidate may involve lowering cholesterol content in the brain.…”
Section: Cholesterolmentioning
confidence: 52%
“…Other studies also show that methylphenidate is effective in reducing low density lipoprotein cholesterol, triglycerides, and total cholesterol as well as ameliorating the effects of fatigue. 92,93 These added effects are particularly advantageous given that of those with HIV, 38% experience hypercholesterolemia and nearly 50% experience a range of depressive symptomatology. 47,94 …”
Section: Cognitive Interventionsmentioning
confidence: 99%